(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Dedicated to the development of models for the construction of logistics management system of production resources of the textile enterprise, in this chapter the algorithmic model of informationanalytical support of the process of management of production resources of the enterprise and the mathematical model of forecasting sales of textile enterprises construction, solving the main problems of organizational design of the production system, modeling on the basis of a logistical approach.